Selection of Proper Potting Mixture for Raising Acacia nilotica Seedlings under Root Trainer Seedling Production System - Ginwal, H. S.; Rawat, P. S.; Bhandari, A. S.; Krishnan, C.; Shukla, P. K. (Indian Forester, 2001)
The containerized seedling production technology , especially the root trainers , is dependent upon suitable growing media for raising quality seedlings in nurseries. Due to lack of species specific results for Indian conditions and species , the use of root trainers is still in the initial stage. In the present investigation , experiments were carried out to findout the proper combination of sand , soil , compost and combinations of charcoal , rice husk and compost as a organic medium , to be used as growing media under root trainers for raising A. nilotica seedlings. The growth , biomass production of Acacia nilotica seedlings in 3 months period was studied and the quality parameters of seedlings raised in various treatments (Potting mixture combinations) were figured out. In respect of sand , soil and compost , combination of sand and compost in the ratio of 1:4 (20% sand + 80% compost) produced the best results and scored maximum points in respect of quality parameters. Testing the organic ingredients , combination of charcoals and compost in the ratio of 1:4 (20% charcoal + 80% compost) was another good growing medium. Thus two potting mixtures with different ingredients were standardized. The results on use of pure compost as a potting medium were not very much appreciable. The compost is required to be supplemented with 20% charcoal or 20% sand for making it more effective in raising Acacia nilotica seedlings. Improper choice of potting mixture may result in poor quality seedling production in nurseries.